2005
DOI: 10.1177/001698620504900307
|View full text |Cite
|
Sign up to set email alerts
|

Do Gifted Student Writers and Creative Writing Experts Rate Creativity the Same Way?

Abstract: Little research has been conducted on how gifted novices compare to experts in their judgments of creative writing. If novices and experts assign similar ratings, it could be argued that gifted novices are able to offer their peers feedback of a similar quality to that provided by experts. Such a finding would support the use of collaborative feedback in gifted classrooms. We asked gifted high school creative writers and three groups of experts (cognitive psychologists, creative writers, and teachers) to rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 26 publications
3
79
0
Order By: Relevance
“…The consensual assessment technique entails independent judges-ideally but not necessarily experts-rating products for creativity, based on the judges' tacit, personal meanings of creativity. Judges often show high consistency and agreement (Amabile, 1982;Baer, Kaufman, & Gentile, 2004;Kaufman, Gentile, & Baer, 2005;Kaufman, Lee, Baer, & Lee, in press). …”
Section: Uniqueness Scoring Penalizes Large Samplesmentioning
confidence: 99%
“…The consensual assessment technique entails independent judges-ideally but not necessarily experts-rating products for creativity, based on the judges' tacit, personal meanings of creativity. Judges often show high consistency and agreement (Amabile, 1982;Baer, Kaufman, & Gentile, 2004;Kaufman, Gentile, & Baer, 2005;Kaufman, Lee, Baer, & Lee, in press). …”
Section: Uniqueness Scoring Penalizes Large Samplesmentioning
confidence: 99%
“…Five elementary classroom teachers were selected as being appropriate experts to rate the creative products, consistent with past findings that show classroom teachers as agreeing with content experts when rating children's creative work (Baer, Kaufman, & Gentile, 2004;Kaufman, Gentile, & Baer, 2005). No rater was a classroom teacher for any of the children in the study, and all products were presented with no identifying information.…”
Section: Ratersmentioning
confidence: 99%
“…Proficiency in creative activities was characterized by Johnson-Laird, who stated that such proficiency involves not only skills that can be obtained by training but also the discovery of new information and knowledge [7]. Kaufman et al [8] investigated writer's creativity by comparing student and expert writers' writings. Oura investigated the proficiency of pianists and practitioners in terms of the cognitive psychology of their creative skills and showed that proficient pianists and Kendo practitioners learn and play by understanding implicit and complicated information [9].…”
Section: Introductionmentioning
confidence: 99%